Relationship between jump height and lower limb joint kinetics and kinematics during countermovement jump in elite male athletes - Shinchi, K.; Yamashita, D.; Yamagishi, T.; Aoki, K.; Miyamoto, N. (Sports Biomechanics, 2024)
This study aims to identify the relationship between jump height and the kinetic and kinematic parameters of the hip, knee, and ankle joints during countermovement jump (CMJ) in elite male athletes. Sixty-six elite male athletes from various sports (strength and power, winter downhill, combat, ball game, and aquatic) performed maximal effort CMJs with hands and arms crossed against their chests on force platforms. Jumping motion in the sagittal plane was recorded using video analysis and the peak torque, power, and angular velocity of the right hip, knee, and ankle joints were calculated during the propulsive phase. Correlations between the CMJ height and kinetic and kinematic parameters were investigated using Pearson`s product-moment coefficient (r) and Spearman`s rank correlation coefficient (p). CMJ height was highly correlated with peak hip power (p = 0.686, p < 0.001) and peak knee angular velocity (r = 0.517, p < 0.001), and moderately correlated with peak hip angular velocity (r = 0.438, p < 0.001) and peak hip torque (r = 0.398, p = 0.001). These results indicate that notable hip torque and power can contribute to increased angular velocity in both the knee and hip joints, ultimately increasing the CMJ height in elite male athletes.